STUDI KELAYAKAN PERALATAN PADA INSTALASI PANEL KONTROL DI BENGKEL TEKNIK LISTRIK, POLITEKNIK NEGERI PADANG - Desmiwarman Desmiwarman; Valdi Rizki Yandri (Jurnal Teknik Elektro, 2016)
Panel circuit is an equipment which can receive electrical energy and subsequently distribute and control the distribution of electrical energy through the circuit main panel and branch into panel circuit branches or directly via the circuit end to the load in the form some point the lights and through the box- contact to equipment utilization of electricity inside the building. Planning methods to repair Panel circuit is composed of several stages, namely (1) Calculate the power used on each wall of the practice, (2) Selection of rating safety MCB and CRC cable, (3) The design of the power circuit and the control circuit for the panel, (4) Sort the numbering of the cable to the output sockets on each wall of the practice (5) Preparationof a series on the panel (6) Testing.Panel circuit in electrical repair shop is designed based on the layout of the walls of the practice. Keluran of the panel for this circuit is 24 Sockets 3 phase on each wall of the practice, which is used to load a practice wall, namely the installation of lighting and power installation.